Manufacturing Analysis of Banana Slicer Machine Capacity 59 kg Hour: Analisis Produksi Mesin Pengiris Pisang dengan Kapasitas 59 kg per Jam - Nabil Azka Hanani; Mulyadi; Edi Widodo; A’rasy Fahruddin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Banana processing is an important agro-industrial activity in Indonesia, particularly for producing banana chips with consistent quality. Specific Background: Conventional manual slicing methods are inefficient and result in inconsistent thickness, limiting productivity and product quality. Knowledge Gap: Previous approaches have not fully integrated manufacturing process analysis with time, cost, and performance evaluation in a single machine design. Aims: This study aims to analyze the manufacturing process of a banana slicer machine with a capacity of 59 kg/hour, including time estimation, cost calculation, and performance testing. Results: The manufacturing process consists of cutting, drilling, welding, turning, and milling, resulting in a total production time of 29.63 hours and a total cost of Rp 5,058,262. Performance testing shows that the use of three blades produces the most consistent slice thickness of 2 mm with good quality output. Novelty: The study integrates detailed manufacturing time analysis, cost estimation, and performance evaluation within a single machine development framework. Implications: The findings provide practical guidance for improving production efficiency and product quality in small to medium-scale banana processing industries. Keywords: Banana Slicer, Manufacturing Process, Production Cost, Machine Performance, Agro-Industry Key Findings Highlights Total fabrication duration reached 29.63 hours with structured process stages Optimal blade configuration identified for uniform slice thickness Economic calculation established selling value with defined profit margin